COMPARATIVE STUDIES OF COOPERATIVES ACT NUMBER 25/1992 WITH COOPERATIVES ACT DRAFT 2010 - Yuni Sudarwati (Pusbindiklat - LIPI, 2012)
Indonesia cooperatives condition that have not been able to be an Indonesia economics pillar need to getsupport. One kind of support needed is from legislation. Cooperatives Act Number 25/1992 changes is to supportdevelopment of cooperatives. This new cooperative act is expected to have more advantage for cooperatives development.The purpose of this research is to analyze advantage and disadvantage of cooperatives act draft 2010.Comparison between cooperatives act draft 2010 with Cooperatives Act Number 25/1992 based on InternationalCooperative Alliance (ICA) principal perspectives. The results show that cooperatives act draft 2010 has moreadvantage than cooperatives act number 25/1992 based on ICA principal perspectives.